Isolation of bacterial contaminants from elevator buttons of Kulliyyah of Medicine and office of Campus Director in International Islamic University Malaysia Kuantan - Yusoff, Iylia Nurliyana; Alias, Norsyuhada (2018)
Background: There had been an increase in the awareness of microbial contamination in the world today. It can often go unnoticed or be found in the most unexpected places. With the increase in infectious disease globally, it is more important for us to take preventive measures in order to prevent further spreading of bacterial contamination. In this study, we have identified and measured the bacterial contamination that can be found on the surface of elevator buttons of Kuliyyah of Medicine and Office of Campus Director in International Islamic University Malaysia Kuantan Campus (IIUMK). Methods: The study was a cross-sectional research. Samples were taken from elevator buttons from the surface of elevator buttons of Kuliyyah of Medicine and Office of Campus Director in IIUMK using sterile cotton swab moistened with nutrient broth. Enumeration of bacteria was done using the viable plate count method. The enumeration of bacterial contaminants was recorded as CFU/ml and classified into low, medium or high contamination level. Morphology characteristic of bacterial contaminants was observed by streaking bacterial colonies on mannitol salt agar and MacConkey agar according to the standard microbiological methods. Finally, Gram staining and PCR amplification of 16rRNA were carried out to further distinguished and identified the type of bacteria. Results: This study was conducted on 89 buttons from five elevators available in Kuliyyah of Medicine and Office of Campus Director in IIUMK. Eighty-four percent of the samples showed growth of bacterial contamination. Enumeration of bacteria was categorised into low, medium and high contamination categories. Fifty elevator buttons were categorised having low contamination and twelve elevator buttons are classified as having medium contamination. Twelve elevator buttons is categorised into high contamination category. It is expected that the elevator buttons were dominated by Staphylococcus and Enterobacter species based on morphological characteristics and Gram types. Molecular identification via PCR is still underway. Conclusions: Preliminary result revealed there is a presence of bacterial contaminants on the surface of the elevator buttons of Kuliyyah of Medicine and Office of Campus Director in IIUMK. Hence, elevator buttons could be the transmitting medium of pathogenic bacteria. The findings signify the importance of routine elevator buttons disinfection to lessen bacterial transmission.